2012
DOI: 10.3113/fai.2012.0669
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Stability of a Locked Step-Plate versus Single Compression Screw Fixation for Medial Displacement Calcaneal Osteotomy

Abstract: The magnitude of the load supported by the locking step-plate suggests that allowing early weightbearing post-operation may be safe in clinical practice before union of the osteotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…26 There are various types of fixation used in MCO, but regardless of method, union rates after MCO are high, with studies reporting rates up to 97% to 100% with comparable rates of return to activity, hardware removal, and functional outcomes. 1,73,105,107…”
Section: Hindfoot Valgusmentioning
confidence: 99%
See 1 more Smart Citation
“…26 There are various types of fixation used in MCO, but regardless of method, union rates after MCO are high, with studies reporting rates up to 97% to 100% with comparable rates of return to activity, hardware removal, and functional outcomes. 1,73,105,107…”
Section: Hindfoot Valgusmentioning
confidence: 99%
“…26 There are various types of fixation used in MCO, but regardless of method, union rates after MCO are high, with studies reporting rates up to 97% to 100% with comparable rates of return to activity, hardware removal, and functional outcomes. 1,73,105,107 One risk of MCO is neurovascular injury. A lateral incision is usually placed directly over the planned osteotomy site, and one study showed a safe zone using a reference point that is one-third the distance from the tip of the lateral malleolus to the posterior inferior margin of the calcaneus.…”
Section: Medializing Calcaneal Osteotomymentioning
confidence: 99%
“…While some lateral locked plates without compression have been discussed in the literature, currently no studies compare the outcomes of a lateral locked compression device to traditional fixation methods for calcaneal displacement osteotomies. 3,13 The primary purpose of this study will be to retrospectively compare clinical outcomes of these 2 fixation methods. Secondarily, an analysis of implant costs alone as well as a comparison to the cost of returning to the operating room for removal will be performed.…”
Section: Introductionmentioning
confidence: 99%
“…1 Alternative fixation methods have been developed, such as lateral step plates and blade plates, but few comparative studies are available. In a cadaver study, Konan and colleagues 21 found that a lateral locked step plate was stronger that a single cannulated 7-mm screw. One study by Abbasian and colleagues 1 compared fixation methods performed following open calcaneal osteotomies using headed screws, headless screws, or a lateral step plate.…”
Section: Fixation Considerationsmentioning
confidence: 98%